2002
DOI: 10.1212/wnl.58.5.773
|View full text |Cite
|
Sign up to set email alerts
|

Early detection and longitudinal changes in amyotrophic lateral sclerosis by 1 H MRSI

Abstract: Objective-To determine 1) the reproducibility of metabolite measurements by 1 H MRS in the motor cortex; 2) the extent to which 1 H MRS imaging (MRSI) detects abnormal concentrations of N-acetylaspartate (NAA)-, choline (Cho)-, and creatine (Cre)-containing compounds in early stages of ALS; and 3) the metabolite changes over time in ALS.Methods-Sixteen patients with definite or probable ALS, 12 with possible or suspected ALS, and 12 healthy controls underwent structural MRI and multislice 1 H MRSI. 1 H MRSI da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 28 publications
4
72
1
1
Order By: Relevance
“…Previous studies measuring absolute metabolites in ALS have inconsistently found increased Cho, yet all additionally documented decreased NAA. 14,23,[48][49][50] Compared with absolute quantitation, ratio determination provides a simpler and more reliable method with less experimental error. It would be worthwhile to follow up these findings with a study that incorporates absolute quantitation but with a larger sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies measuring absolute metabolites in ALS have inconsistently found increased Cho, yet all additionally documented decreased NAA. 14,23,[48][49][50] Compared with absolute quantitation, ratio determination provides a simpler and more reliable method with less experimental error. It would be worthwhile to follow up these findings with a study that incorporates absolute quantitation but with a larger sample size.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Cho was chosen as an internal reference metabolite because previous spectroscopic studies have revealed larger effect sizes and accuracy profiles for NAA/Cho compared with NAA/Cr. 8,[12][13][14][15] Voxels were assigned to the MCC, thalamus, and motor cortex (PCG) (Fig 1). Metabolite ratios for each region (ie, MCC, thalamus, and PCG) were calculated by determining the average ratio for all voxels assigned to that region.…”
Section: Imagingmentioning
confidence: 99%
“…The neuronal marker NAA has been shown to be associated to reduced neuronal integrity and neurodegeneration in ALS. Compared to healthy individuals, ALS patients show reduced levels of NAA the primary motor cortex (Gredal et al, 1997;Han and Ma, 2010;Nelles et al, 2008;Pioro et al, 1994;Pohl et al, 2001;Sarchielli et al, 2001;Suhy et al, 2002;Wang et al, 2006) and brain stem (Cwik et al, 1998;Pioro et al, 1999). Reduced NAA to total creatine ratio in motor cortex of ALS patients correlates with ALS Functional Rating Scale that depicts ALS progression (Sivák et al, 2010).…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…It appears that spectrum quality and reproducibility may degrade when voxels are located away from the magnet isocenter or near the tissue-bone interface. Positioning of voxel becomes even more critical when the motor cortex is sampled, which may have contributed to relatively lower reproducibility of NAA measurement in this region (Suhy et al 2002). Previously we found that the voxels localized in the central part of the ROI have higher SNR ratios and better spectral quality (see illustrations in Figure 1).…”
Section: Discussionmentioning
confidence: 97%